2000
DOI: 10.1289/ehp.00108617
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-induced skin lesions among Atacameño people in Northern Chile despite good nutrition and centuries of exposure.

Abstract: It has been suggested that the indigenous Atacameño people in Northern Chile might be protected from the health effects of arsenic in drinking water because of many centuries of exposure. Here we report on the first intensive investigation of arsenic-induced skin lesions in this population. We selected 11 families (44 participants) from the village of Chiu Chiu, which is supplied with water containing between 750 and 800 microg/L inorganic arsenic. For comparison, 8 families (31 participants) were also selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 18 publications
2
78
0
3
Order By: Relevance
“…People in northern Chile exposed to arsenic had a good nutritious dietary intake. However, the prevalence of skin lesions among men and children in the population studied was similar to that reported at corresponding concentrations of arsenic in drinking water in both Taiwan and West Bengal, India -populations in which malnutrition has been thought to increase susceptibility (33) .…”
Section: Discussionsupporting
confidence: 76%
“…People in northern Chile exposed to arsenic had a good nutritious dietary intake. However, the prevalence of skin lesions among men and children in the population studied was similar to that reported at corresponding concentrations of arsenic in drinking water in both Taiwan and West Bengal, India -populations in which malnutrition has been thought to increase susceptibility (33) .…”
Section: Discussionsupporting
confidence: 76%
“…Four adult men had arsenicinduced skin lesions (15). In one family, both the daughter and her father had skin lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Selection of the Chiu Chiu study site in Chile is explained in detail elsewhere (15). For many years, Chiu Chiu's drinking water was piped in and until only recently had high arsenic content (750-800 µg/L).…”
Section: Methodsmentioning
confidence: 99%
“…Lower BMI was reported among the arsenicosis patients compared to the unexposed population in a previous study in Bangladesh [40]. However, a study from Atacameño in northern Chile reported no evidence of malnutrition among individuals with arsenic induced skin lesions [42].…”
Section: G Association Between Bmi and Arsenic Concentration In Urinementioning
confidence: 71%